Fe-bearing phases in modern lacustrine microbialites from Mexico. (15th May 2019) - Zeyen, Nina; Benzerara, Karim; Menguy, Nicolas; Brest, Jessica; Templeton, Alexis S.; Webb, Samuel M.; Gérard, Emmanuelle; Moreira, David; López-García, Purificación; Tavera, Rosaluz; Morin, Guillaume
Abstract: Transition metal ions impurities in microbialites have been previously suggested as paleoenvironmental and/or paleobiological proxies. However, how metals are incorporated into microbialites remains poorly known. Here, in order to assess the distribution and speciation of Fe in modern microbialites, we conducted bulk X-ray diffraction, infrared spectroscopy, X-ray absorption near-edge structure (XANES) spectroscopy, electron microscopy and X-ray microscopy analyses on samples collected from shallow depths in five alkaline lakes in Mexico: Lake Alchichica, Lake La Preciosa, Lake Atexcac, Lake La Alberca de Los Espinos and Lake Pátzcuaro. A range of Fe contents were measured in these microbialites, from low (∼0.12 wt.%) to relatively high (∼2.2 wt.%). Fe was distributed heterogeneously in microbialites, mostly localized as hotspots or sometimes arranged as discrete laminae. Fe was mostly trivalent in all microbialites and was incorporated into diverse authigenic phases, the proportion of which varied among microbialites. Authigenic phases included Fe-bearing Mg-phyllosilicates such as kerolite and/or stevensite, i.e. (Mg, Fe(II), Fe(III))3 Si4 O10 (OH)2 ·nH2 O and Fe-Mg layered double hydroxides (LDH), i.e. pyroaurite [Mg(II)6 Fe(III)2 (CO3 )(OH)16 ·4H2 O] and/or iowaite [Mg(II)6 Fe(III)2 Cl2 (OH)16 ·4H2 O], together with Fe-(oxyhydr)oxides. Carbonate phases were negligible carriers of Fe in all lakes. Iowaite/pyroaurite phases, which have often been found as low temperature alteration products in serpentinites, were surprisingly observed in Lake Alchichica, whereas Fe-bearing kerolite/stevensite was present in Lake La Preciosa, Lake Atexcac, Lake La Alberca de Los Espinos and Lake Pátzcuaro. Fe present in these shallow water microbialites may be originated from groundwater seepage derived from adjacent Fe-rich volcanic rocks. We suggest that the occurence of iowaite/pyroaurite vs authigenic Fe-bearing kerolite/stevensite depends on the orthosilicic acid concentration in the lakes. Pyroaurite/iowaite may form and stay preserved in Lake Alchichica because of the low [H4 SiO4 ] as well as high alkalinity, [Mg 2+ ], [CO3 2− ], [Cl − ] and pH (∼9) prevailing in this lake, while in other lakes, where [H4 SiO4 ] is higher (above ∼0.4 mM), Fe-bearing kerolite or smectite phases are formed. Overall, the message carried by the Fe-bearing mineral phases in these modern microbialites is multifold: Fe-bearing phases within microbialites may contain some information on environmental conditions (e.g., [H4 SiO4 ]) as well as on geochemical processes implicated during their formation (e.g., seepage of anoxic Fe-bearing groundwater). Considering the reactivity of pyroaurite/iowaite and kerolite/stevensite and their possible transformation into diverse mineral phases upon microbial activity, burial and diagenesis, a careful appraisal of Fe speciation using a similar combination of bulk and microscopy analyses is required in order to better assess the origin of Fe in ancient microbialites.